Plan de Negocios para la Instalación de una empresa comercializadora de mariscos en el Cantón Valencia de la Provincia de los Ríos, 2021. - Marca Baraja, Cesar Vinicio (2022)
The present investigation titled as: Business plan for the installation of a seafood marketing company in the Valencia Canton of the Province of Los Ríos, year 2021, was carried out with the purpose of publicizing the viability of the commercialization of this type of product of great economic value, offering several quality products at very affordable prices for consumers, with the purpose of fulfilling the stated objectives, it was necessary to resort to bibliographical research that allowed obtaining theoretical information from various authors, as well as the diagnostic research was relevant because it was necessary to diagnose the supply and demand of shellfish through the survey addressed to the 15 shellfish merchants and the 155 families of the Valencia Canton. Through the market study carried out, it was found that there was an annual demand of 1,906,396 pounds of seafood and an annual supply of 479,388 pounds, giving an unsatisfied demand of 1,427,008 pounds of seafood per year that families want to consume and are acquiring in other markets, with which the existence of a market for the installation of the seafood restaurant is expected. The technical study made it possible to determine that the size of the project calculated with 9.6% having an installed capacity that will allow the marketing of 136,760 pounds of seafood per year, estimated from the unsatisfied demand calculated for this market. The availability of resources, the requirements of the project and the legal framework essential for the operation of the microenterprise have been considered in this study. In addition, for the start of the business, the economic study plans to resort to a financial loan via Ban Ecuador, giving a capital investment of 20,000.00 dollars. The financial study reflects a NPV of $141,398.29 with an estimated IRR of 158%, values that demonstrate the economic and financial viability of this investment for the implementation of the business plan.